Man-Elephant Conflict and Mitigation - Koundinya Wildlife Sanctuary, Andhra Pradesh - Syam Prasad, N.; Reddy, K. S. (Indian Forester, 2002)
Elephants returned to Andhra Pradesh in 1984 after a gap of 200 years and started living in dry deciduous forests in southern-most parts of Chittoor District. Initially elephants caused considerable damage to man and crops. In retaliation, man killed 12 elephants. With advent of Joint Forest Management practices, development programmes including Project Elephant scheme are implemented mostly through peoples participation in Koundinya Wildlife Sanctuary. Gap planting, Water harvesting structures, plugging of entry across vulnerable borders, awareness campaign and good communication facilities yielded encouraging results in mitigating man-elephant conflict and increased elephant population year after year.